FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PEMILIH KECAMATAN TENGGARONG (Study Pilkada Kukar 2005) - Toni Nurhadi Kumayza (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2015)
Factors affecting the behavior of voters sub Tenggarong, objective research to describe the behavior of voters in each community tengagarong local elections. Also learn what factors influence the behavior of voters in each community Tenggarong local elections.To give a concrete picture of some of the concepts presented operasioal of each observed variable and include indicators that are used to a variable in the study, the authors present the following indicators Social factorsa) Education / level of education in view of recent education graduates.b) Class / views of the profession of social status and income level.c) Religion viewed from the understanding of the religion which embraced and recognized by the government just as: Islam, Catholic, Protestant, Hindu, and Buddhist.d) Gender / sex.e) Ethnic / tribal inheritance and,f) Age / age of the voting age is viewed from the age of 17 years or who have been married. The study area is the city district as the district capital Tenggarong Kukar analyzer used is crostab tabulation in which the tool can be used nominal data with a data connection through difference frequency ordinal case. Based on social factors seem that people are rational enough Tenggarong city in determining the choice of this is reflected in the magnitude of the influence of factors determine their choice of education for the next 78.5% of religious factors also contribute significantly by 68.5% then 42.2% of ethnic factors. In this case Tenggarong community in an election have started regardless of primordial ties and class structure in which the factors of age (28.2%), class (26%), and gender (19.9%) even become a factor that is not approved by the majority of people in determining their choice. key word: behavior of voter